Reading and writing skills - Tiongson, Marella Therese A.; Rodriguez, Maxine Rafaella C. (Sampaloc Manila : Rex Book Store, Inc., 2019)
"Reading and Writing Skills aims to encourage students to explore many strategies for critical reading and writing through the given selections and activities, which cater to various 21st century learning needs and styles. It also contains lessons that are relevant and engaging. Overall, this book is an invaluable resource to accompany students in their journey of learning English."
Includes bibliographical references.
English text.
Keywords: Reading; Rhetoric; English language -- Composition and exercises